Strain effects on domain structures in ferroelectric thin films from phase‐field simulations. Issue 10 (30th April 2018) - Lin, Fang‐Yin; Cheng, Xiaoxing; Chen, Long‐Qing; Sinnott, Susan B.
Abstract: Strain and applied external electric fields are known to influence domain evolution and associated ferroelectric responses in ferroelectric thin films. Here, phase‐field simulations are used to predict equilibrium domain structures and polarization‐field ( P ‐ E ) hysteresis loops of lead zirconate titanate (PZT) thin films under a series of mismatch strains, ranging from strongly tensile to strongly compressive. In particular, the evolution of domains and the P ‐ E curves under different applied strains reveal the mesoscale mechanism, the appearance of in‐plane polarization during domain switching, that is responsible for a relatively small coercive field and remnant polarization. A Landau energy distribution is analyzed to better understand the domain evolution under various strain conditions. The results provide guidance for choice of mismatched strains to yield the desired P ‐ E hysteresis loops and the domain structures.